Building offline applications with Angular : develop reliable, performant web applications for desktop and mobile - Kotaru, Venkata Keerti (Apress, 2022)
Get a complete overview of offline installable applications. Businesses need reliable applications that enable users to access data and their applications in spite of a bad network connection. Traditional websites work only when connected to the network. With a large number of users depending on mobile phones and tablets for work, social interactions, and media consumption, its important that the web applications can work on a weak network connection and even offline. This step-by-step guide shows you how to build an Angular application that considers offline access and uses its ready-made features and configurations. Build Offline Applications with Angular helps bridge the gap between native apps and web applications. You will: Get started with an installable Angular application Understand the importance of performant, reliable, and offline access of a web application Discover solutions for building Angular applications for speedy response in low bandwidth scenarios Use IndexedDB as an offline data store within a browser.